2016
DOI: 10.1038/leu.2016.347
|View full text |Cite
|
Sign up to set email alerts
|

Loss of p300 accelerates MDS-associated leukemogenesis

Abstract: The role that changes in DNA methylation and histone modifications play in human malignancies is poorly understood. p300 and CBP, two distinct but highly homologous lysine acetyltransferases (KATs), are mutated in several cancers, suggesting their role as tumor suppressors. In the current study, we found that deletion of p300, but not CBP, markedly accelerated the leukemogenesis of Nup98-HoxD13 (NHD13) transgenic mice, an animal model that phenotypically copies human myelodysplastic syndrome (MDS). p300 deleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 37 publications
3
28
0
Order By: Relevance
“…3 [p.Asn359Argfs*51]). This is consistent with a recent study demonstrating a tumor suppressor role of Ep300 in myeloid malignancies (Cheng et al, 2017). Additionally, although EP300 mutations in CHIP have not been reported in large studies, a case of clonal hematopoiesis with EP300 mutation was recently reported (Gondek et al, 2016).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…3 [p.Asn359Argfs*51]). This is consistent with a recent study demonstrating a tumor suppressor role of Ep300 in myeloid malignancies (Cheng et al, 2017). Additionally, although EP300 mutations in CHIP have not been reported in large studies, a case of clonal hematopoiesis with EP300 mutation was recently reported (Gondek et al, 2016).…”
Section: Resultssupporting
confidence: 94%
“…S1B). We also included Ep300 , since Ep300 deletion accelerated the progress of MDS and AML, suggesting that Ep300 may function as a tumor suppressor in myeloid malignancies (Cheng et al, 2017). We designed four sgRNA per gene and electroporated them individually into c-kit + HSPCs.…”
Section: Resultsmentioning
confidence: 99%
“…While CBP and P300 are nearly identical in structure, they have distinct and non-redundant functions 47 . Indeed, recent study of CBP and P300 in Nup98-Hoxd13-induced leukemogenesis found that loss of p300 , but not Cbp , contributes to leukemogenesis 48 . Conversely, Cbp and p300 were cooperatively required for leukemogenesis induced by Nup98-Hoxa9 and Moz-Tif2 oncogenes 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Such a model is supported by the Rubinstein-Taybi syndrome due to heterozygous deletion mutations of CBP that reduce CBP gene dosage, leading to human developmental defects. This model also explains the distinct requirements of CBP and P300 in normal hematopoiesis and leukemia cell development (Wang et al, 2011;Cheng et al, 2017), as well as the functional requirement for P300 in CBP-deficient cancers (Ogiwara et al, 2016). Definition of the mechanisms of this molecular switch regulating discrete gene expression programs is expected to reveal distinct mechanisms of dysregulated gene control in AML and other transcription-dysregulated cancers.…”
Section: Discussionmentioning
confidence: 88%